Supercapacitors for renewable energy applications: A review - Zhang, Jie; Gu, Min; Chen, Xi (Micro and Nano Engineering, 2023)
Energy harvesting and conservation are essential for all kinds of power sources, particularly renewable energy sources, given their global distribution. Usually, batteries are employed to mitigate the imbalance between abundant renewable energy generation and inefficient energy transmission. However, batteries suffer from a drawback in terms of low power density. In recent years, supercapacitor devices have gained significant traction in energy systems due to their enormous power density, competing favorably with conventional energy storage solutions. This research paper comprehensively overviews various supercapacitor modalities, encompassing electrode materials, electrolytes, structures, and working principles. Furthermore, it explores the diverse applications of supercapacitors in the consumption of renewable energy, showcasing their potential in various domains, thereby reflecting the thriving prospects of these devices in modern society. Finally, the paper addresses the challenge of energy management in conjunction with supercapacitors.